Essential words for the TOEFL : Test of English as a foreign language - Matthiesen, Steven J.; Nguyễn Văn Phước (Tp.HCM : Nxb. Trẻ, 2000)
Sách gồm các bài tập giúp luyện thi thành công TOEFL.
Keywords: Anh ngữ; English language; Toefl; Tests; Bài tập Anh ngữ; English language -- Tests